A CASE STUDY ON LIFE-THREATENING PREGNANCY-INDUCED HYPERTENSION IN PRETERM PREGNANCY AND MANAGEMENT CHALLENGES: Pregnancy induced hypertension - AREEFA ALKASSEH; MARYAM SHAATH (Innovare Journal Health Sciences, 2019)
Pregnancy-induced hypertension (PIH) is life threatening for the mother and her baby. Pre-eclampsia in pregnancy is a multisystem, disorder associated with significant maternal and neonatal morbidity and mortality. The current case study was done to clarify the consequences of PIH as a life-threatening condition at one of the governmental hospitals. A follow-up with observation recording was done since the first admission until the end of treatment duration. The patient presented with life-threatening PIH at 32 weeks of gestation. She was very tired and irritable and stayed in the hospital for several days; the case condition was progressed toward worse, lack of high-risk cases management team, the treatment plan, and decision-making were delayed until the 2nd day in the presence of the senior doctors. The final consequence for the present case was delivered by complicated cesarean section, the uterine repair was done due to placenta accrete and the baby was transferred to the neonatal intensive care unit with low Apgar scoring. The study concluded that early detection and proper intervention with the presence of collaborative team are required to reduce the maternal complications in low resources countries.